2019
DOI: 10.1111/jocd.12979
|View full text |Cite
|
Sign up to set email alerts
|

Whitening effects of cosmetic formulation in the vascular component of skin pigmentation

Abstract: Background: Melanin plays an important role in protecting the skin against the harmful effects of solar radiation, but its abnormal accumulation may become an aesthetic problem, such as melasma and age spots. Aims: The aim of this study was to evaluate the antiangiogenic and whitening effects of a depigmentation formulation (BLTX) using an in vitro model of human cell and skin culture. Methods: Human fibroblasts, keratinocytes or melanocytes were treated with BLTX and subjected to oxidative stress by UV radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…As already described in the literature, 14‐20 UVA/UVB, IR‐A, and VL radiations significantly increase of 8.22, 5.32, and 5.98%, respectively ( p < 0.001), in the synthesis of melanin, when compared to baseline group (Figure 1). The association of radiation (ASS) produced significant increases in melanin synthesis when compared to three types of radiation applied alone, reaching a 10.56% increase compared to baseline control.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…As already described in the literature, 14‐20 UVA/UVB, IR‐A, and VL radiations significantly increase of 8.22, 5.32, and 5.98%, respectively ( p < 0.001), in the synthesis of melanin, when compared to baseline group (Figure 1). The association of radiation (ASS) produced significant increases in melanin synthesis when compared to three types of radiation applied alone, reaching a 10.56% increase compared to baseline control.…”
Section: Resultssupporting
confidence: 79%
“…The radiation doses were based on preliminary studies obtained in our laboratory. [14][15][16][17][18][19][20] After 48 h of irradiation, cell lysates were collected for quantification of melanin, ED1, and PPAR α, δ, and γ.…”
Section: Photoexposure Of Cell Culturesmentioning
confidence: 99%
“…Specifically speaking, melanogenesis is an important skin protection factor that prevents harmful effects of solar radiation. However, abnormal accumulation of melanin would result in melasma and age spots [ 22 ]. Therefore, tyrosinase which controls the primary and rate-limiting processes of melanin production [ 23 ] shall be adopted to suppress melanogenesis that causes freckles and age spots.…”
Section: Introductionmentioning
confidence: 99%
“…Our efforts to establish a model with high reproducibility and adaptability to different experimental conditions generated positive results, as we have been able to use ex vivo human skin as a tool in the evaluation of several skin disorders, such as photoageing, skin dryness, atopic dermatitis, hair follicle ageing, skin and hair follicle permeation, among others. [14][15][16][17][18][19][20][21][22][23][24][25]37 These studies comprise specific methodologies in which mediators of the various disorders are evaluated by using different techniques, such as immunofluorescence and immunoassays, as well as more complex studies involving omics platforms. These studies help to further our understanding of the complex interactions between cutaneous tissue and the extrinsic environment.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Studies performed by our group have shown that ex vivo skin, cultured under specific conditions, maintains the biological characteristics of in vivo skin for the length of time required to perform the tests, thus representing a feasible model with which to evaluate different parameters. [14][15][16][17][18][19][20][21][22][23][24][25] The purpose of this proof-of-concept study was to assess the potential of ex vivo skin, as an alternative to reconstructed skin, on irritation and corrosion testing according to TGs 439 and 431.…”
Section: Introductionmentioning
confidence: 99%